High Expression of DC-STAMP Gene Predicts Adverse Outcomes in AML - Liang, Qian; Zhang, Lele; Wang, Wenjun; Zhao, Jingyu; Li, Qiaoli; Pan, Hong; Gao, Zhen; Fang, Liwei; Shi, Jun (Frontiers in Genetics, 2022)
Acute myeloid leukemia (AML) is a genetically heterogeneous hematological malignancy with poor prognosis. We explored the RNA sequence data and clinical information of AML patients from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) database to search for the core molecule for prognosis. The DC-STAMP expression was significantly higher in AML patients, which was linked to old age, unfavorable cytogenetic risk, and death (all p < 0.05). Furthermore, it was revealed that high DC-STAMP expression was an independent unfavorable factor for overall survival (OS) by univariate analysis [hazard ratio (HR): 2.683; 95% confidence interval (CI): 1.723–4.178; p < 0.001] and multivariate analysis (HR: 1.733; 95% CI: 1.079–2.781; p = 0.023). The concordance index (C-index 0.734, 95% CI: 0.706–0.762), calibration curves, and decision curve analysis showed the certain predictive accuracy of a nomogram model based on multivariate analysis for OS. In addition, we found that the differentially expressed gene (DEG) enrichment pathways of high- and low-DC-STAMP expression group enrichment pathways were focused on channel activity and platelet alpha granule by the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG), while gene set enrichment analysis (GSEA) pathways were mainly involved in mTORC1 signaling and TNF-α signaling via the NF-kB pathway. Moreover, a protein–protein interaction (PPI) network demonstrated that DC-STAMP interacted with two hub genes (PPBP and PF4), which were highly regulated and associated with poor survival. Finally, high DC-STAMP expression showed a significantly positive correlation with four immune cell [NK CD56 (dim) cells, macrophages, cytotoxic cells, and CD8 (+) T cells] infiltration and high level of immune checkpoint genes (PDCD1, CD274, CTLA-4, and TIGIT). Therefore, our results suggest that high expression of DC-STAMP predicts adverse outcomes for AML patients.